Effect of homopolymer poly(vinyl acetate) on compatibility and mechanical properties of poly(propylene carbonate)/poly(lactic acid) blends - J. Gao; Q. Fu; H. Bai; Q. Zhang; Y. Gao; L. Chen (eXPRESS Polymer Letters)
A small amount of homopolymer poly(vinyl acetate) (PVAc) is used to compatibilize the biodegradable blends of poly(propylene carbonate) (PPC) and poly(lactic acid) (PLA). Scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) results show that PVAc is selectively localized in the PLA phase and at the interface between PPC and PLA phases. As a result, these interface-localized PVAc layers act as not only a compatibilizer to improve the phase dispersion significantly but also a bridge to increase the interfacial adhesion between PPC and PLA phases dramatically. Both of them are believed to be responsible for the enhancement in mechanical properties. This work provides a simple avenue to fabricate eco-friendly PPC/PLA blends with high performance, and in some cases, reducing the demand for petroleumbased plastics such as polypropylene.